Socio- Economic Status of The Majhi Community in Lalbandi, Municipality - Ghimire, Dharma Raj (Janajyoti Journal, 2025)
Nepal is the country of ethnic diversity and identities. Among them Majhi is an indigenous ethnic group,primarily residing in the inner Terai and hilly regions along the banks of rivers and streams. This article aims tostudy socio-economic status of Majhi Community of Lalbandi in Sarlahi. Descriptive and analytical researchdesign have been employed to conduct this study. Primary and secondary data were collected via interviewschedule and key informant interview. Observation and field visit was also used to find the activity and patternsof the Community. In the course of study, 80 Majhi people were selected as respondents who were heads ofhousehold consisting 20 respondents from each ward by the help of purposive sampling. It is found that thesocio-economic pattern of Majhi people of the study site is changing due to shifting pattern of livelihood. Theyhave shifted their traditional occupation fishing, boating to agriculture, labour work, carpentry, driving,teaching, foreign employment, etc. which has changed their income level and ways of livelihood in positiveway. Inclusive initiatives have integrated them to mainstream and uplifted their lifestyle.